2020
DOI: 10.1111/jan.14451
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making among the substitute decision makers in intensive care units: An investigation of decision control preferences and decisional conflicts

Abstract: AimsTo explore decision control preferences and decisional conflicts and to analyse their association among the surrogate decision makers in the intensive care unit.DesignThe study carried out a cross‐sectional survey among the surrogates.MethodsThe participants were 115 surrogate decision makers of critical patients, from August to September 2019. A Chi‐squared test and logistic regression were used to assess decision control preferences and decisional conflicts, and Spearman's rank correlation coefficient wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Other measures of decision-making include decisional self-efficacy and decisional conflict [ 49 ]. Higher levels of decisional conflict have been associated with end-of-life decisions, whereas advanced directives have been associated with lower decisional conflict [ 5 , 50 , 51 ]. However, lower decisional conflict may also indicate a lack of engagement with hard choices, rather than better decision-making [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other measures of decision-making include decisional self-efficacy and decisional conflict [ 49 ]. Higher levels of decisional conflict have been associated with end-of-life decisions, whereas advanced directives have been associated with lower decisional conflict [ 5 , 50 , 51 ]. However, lower decisional conflict may also indicate a lack of engagement with hard choices, rather than better decision-making [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although shared decision-making is essential to support patient-centered care [67], evidence suggested that medical necessity and clinicians' sense of patients' best interests still drive the direction of treatment decision making when the stakes are high [13] Unlike previous studies, our DA incorporates the consideration of family-centered care to improve surrogates' participation in and preparation for decision making. The role of surrogate decision makers in critical illness has been indicated with associations of surrogates' decisional dilemmas [10], decisional con icts [12], decisional regrets [70], personal distress [71], high incidence of PTSD-like symptoms [72], and post-ICU syndrome [73]. Cox et al [74] conducted a randomized clinical trial to examine the effects of a web-based DA for surrogate decision makers of patients with prolonged mechanical ventilation in ICU, which showed greater reduction in decisional con ict among surrogates, but with no impact on the improvement of surrogates' psychological distress, prognostic concordance between surrogates and clinicians, or patients' clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relative prevalence of RRT for ICU patients suffering from AKI, it is di cult for family surrogates to nd reliable information about RRT and therefore challenging for them to share in the decision-making process with clinicians [11]. Furthermore, family participation in RRT decision making was uniformly reported as a stressful experience [12], and discrepancies between the values and priorities of the medical system and those of the patient were identi ed [11]. Usually, family surrogates face dilemmas when participating in preference-sensitive decision making for critically ill patients.…”
mentioning
confidence: 99%
“…Therefore, decision supports tailored to the unique needs of family surrogate decision makers are needed. [50][51][52][53] For decisions around RRT in the ICU, key points include improving communication and support for surrogates and discussing or clarifying the preferences and values of critically ill patients. [54][55][56] Although our plan will not develop a DA tailored to both surrogates and their loved ones, we expect that our endeavours will provide a reference for future efforts to appropriately involve incapacitated patients in treatment decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Since most critically ill patients are incapacitated, decision making in the ICU is complex. Therefore, decision supports tailored to the unique needs of family surrogate decision makers are needed 50–53. For decisions around RRT in the ICU, key points include improving communication and support for surrogates and discussing or clarifying the preferences and values of critically ill patients 54–56.…”
Section: Discussionmentioning
confidence: 99%